Petrography, mineralogy, and geochemistry of a new lunar magnesian feldspathic meteorite Northwest Africa 11460. (21st October 2021) - Cao, Haijun; Ling, Zongcheng; Chen, Jian; Fu, Xiaohui; Zou, Yongliao
Abstract: Lunar meteorite Northwest Africa (NWA) 11460 has been classified as a polymict breccia, composed of feldspathic clasts, mafic‐rich clasts (gabbroic and troctolitic fragments), granulites, and a wide range of impact melt breccias and dimict breccias. The non‐mare clasts have chemical affinities in major element composition to the Apollo ferroan anorthosites (FAN) and magnesian‐suite plutonic rocks. In contrast, incompatible trace element (ITE) compositions of the Mg‐richer clasts are more consistent with those of FANs rather than magnesian‐suite rocks. NWA 11460 has a Mg‐rich feldspathic bulk composition (FeO = 4.53 wt%, Al2 O3  = 25.87 wt%, and Mg# = 73.8) and relatively ITE‐poor (i.e., Th = 0.31 ppm and Sm = 0.65 ppm) characteristics. Feldspathic impact melt materials are approximately similar in composition to the estimated composition for the upper feldspathic lunar crust (as defined by Korotev et␣al., 2003). The ITE‐poor and Mg‐rich characteristics different from Apollo 16 feldspathic impact melts indicate that this meteorite has been possibly derived from a region distal to the nearside lunar highlands. Our analysis further suggests that NWA 11460 most likely originated from the farside of the Moon. Compositionally, Mg‐rich ITE‐poor clasts within NWA 11460 as well as those observed in other feldspathic lunar meteorites (which probably came from many different lunar regions) reveal that Mg‐rich rocks with low‐ITE components represent an important constituent of lunar crustal rocks. The diversities of highly magnesian non‐mare clasts and the low‐ITE chemistry provide geochemical clues for the genetic relationship between KREEP components and magnesian plutonic magmatism on the lunar farside.